Correlations between Maternal Age, Education, and Knowledge on the Compliance of COVID-19 Vaccine Uptake in Children Aged 6 – 11 Years - Supiatun.M, Lilis Sri; Marhana, Isnin Anang; Husada, Dominicus; Aâ€™yuni, Zera Qurrota (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: The coverage rate for giving the COVID-19 vaccine to children in several regions of Indonesia is still in the low category, one of which is in Abeli District, Kendari City. One of the factors that can affect the low administration of vaccines to children is due to mothers' concerns about their children so they are hesitant and reluctant to be given the COVID-19 vaccine. This study aims to analyze the relationship between age, education, and knowledge of mothers with compliance with the COVID-19 vaccine in children aged 6-11 years in Abeli District, Kendari City. Subjects and Method: A cross-sectional study was conducted in Abeli District, Kendari City, from August to October 2022. A total of 90 subjects were selected using a proportionate stratified random sampling technique. The dependent variable is adherence to giving the COVID-19 vaccine to children. The independent variables include age, education, and mother's knowledge. The instrument used is a questionnaire. Data analysis used was the Chi Square test. Results: Adherence to maternal COVID-19 vaccine administration increased with knowledge (OR= 3.57; 95% CI= 1.46 to 8.75; p= 0.007). Meanwhile, age (OR= 0.34; 95% CI= 0.14 to 0.83; p= 0.003) and education (0.31; 95% CI= 0.12 to 0.31; p= 0.020) reduced maternal adherence in administering the COVID-19 vaccine to children. Conclusion: There is a significant relationship between age, education, and mother's knowledge with compliance with the COVID-19 vaccine in children aged 6-11 years in Abeli District, Kendari City. Keywords: maternal age, maternal education, knowledge, COVID-19 vaccine. Correspondence: Lilis Sri Supiatun Mamesah. Midwifery Program Study, Faculty of Medicine, Universitas Airlangga, Indonesia. Jl. Mayjen Prof. Dr. Moestopo No.47, Pacar Kembang, Tambaksari, Surabaya 60132, East Java, Indonesia. Email: lilis.sri.supiatun-2019@fk.unair.ac.id. Mobile: +6285333622541.